Associations between optic disc characteristics and macular choroidal microvasculature in young patients with high myopia. (29th May 2021) - Liu, Xinting; Zhang, Fen; Wang, Yanli; Xie, Zhu; Wu, Wenfeng; Wang, Qian; Zheng, Miaoran; Lu, Fan; Mao, Xinjie
Abstract: Background: This study aimed to examine changes to optic disc characteristics and macular choroidal microvasculature, and their relationships in young patients with high myopia (HM). Methods: A total of 90 patients were enrolled in this cross‐sectional study. Based on their refractive power, the patients were divided into three groups: 27 in the control group, 34 in the HM group and 29 in the extremely high myopia group. Images of each patient's macula and optic disc were taken by ocular coherence tomography angiography. The macular choroidal and retinal thickness, capillary vessel density and capillary flow area were measured using Matlab software. Parapapillary atrophy (PPA) and the ovality index (OI) obtained from the scanning laser ophthalmoscopy images and the degree of optic disc tilt obtained from the optic nerve head ocular coherence tomography B‐scans were analysed by Image J and Matlab software. Results: The PPA area, OI and degree of optic disc tilt were significantly different among the three groups (all p  ≤ 0.001). The macular choroidal thickness and microvasculature were significantly different among the three groups (all p  < 0.05). Macular choroidal thickness was significantly correlated with PPA area and the degree of optic disc tilt ( r  = −0.331, p  = 0.003; r  = −0.394, p  = 0.001, respectively). Macular choroidal capillary vessel density and choriocapillaris flow area were associated with PPA area ( r  = −0.251, p  = 0.047; r  = −0.326, p  = 0.009, respectively). Conclusions: PPA area, OI and the degree of optic disc tilt were increased in patients with HM, and these changes were correlated with macular choroidal thickness and choroidal microvasculature.